Properties of stabilized compressed earth blocks made from soils in Nueva Vizcaya - Grospe, Myrna B. (Animo Repository, 2002)
Soil is an abundant natural resource. It can be found anywhere. Stabilized concrete earth blocks (SCEB) is a building material which can be made out of this natural resource. It was proven that using SCEB in house construction will decrease the cost by as much as 30 percent. But despite this fact, SCEB is not as popular as the concrete hollow block (CHB) as a building material due to the fact that appropriate technology and specifications for the manufacture and use are lacking or non-existent in the Philippines. No marketing promotion for its manufacture and use are being done precisely because of this.This study was conducted in view of developing the SCEB as an alternative building material for low-cost housing which is both affordable and passing quality standards. It is apparent that before any progress can be made in its manufacture and use, standards and specifications as to the properties of the soil to be used in order to produce the best quality blocks possible must be first established. This study was conducted in view of developing these standards and specifications.Five soil samples were taken from five different locations within the province of Nueva Vizcaya. The particle size distribution, linear shrinkage, liquid limit, plastic limit and plasticity index of each soil sample were determined. From these soil samples, SCEB containing 4 percent, 6 percent, 8 percent and 10 percent cement by weight as stabilizer were made. The wet and dry compressive strength, wet and dry specific density and the moisture absorption capacity of the resulting SCEB were determined. The relationship between the properties of the soil and the properties of the resulting SCEB, and relationship between the properties of the resulting SCEB were then analyzed using regression and correlation analysis.The results of this study indicate that the linear shrinkage, liquid limit, plasticity index and the sand/silt/clay content of the soil are equally important in the determination of its suitability for use in the manufacture of SCEB. On the other hand, the results of this study indicate that the specific density and the moisture absorption capacity of the soil are influenced to a minimal extent by the above mentioned properties of the soil. However, analysis of the relationship between the properties of the resulting SCEB indicates a very strong relationship between them.